Implementasi Hak Fasilitas Dan Aksesbilitas Bagi Penyandang Disabilitas Pada Instansi Kesehatan Di Kota Samarinda (Ditinjau Dari Peraturan Daerah Provinsi Kalimantan Timur Nomor 1 Tahun 2018 Tentang Perlindungan Dan Pemenuhan Hak-Hak Penyandang Disabil - Wahyuni Safitri; Desma Eka Putri (Law Department, University of Widya Gama Mahakam Samarinda, 2021)
This study aims to determine the implementation of facility rights and accessibility for people with disabilities at health institutions in Samarinda City (in terms of East Kalimantan Provincial Regulation Number 1 of 2018 concerning the Protection and Fulfillment of the Rights of Persons with Disabilities). This research is an empirical legal research which is sourced from primary data and secondary data. The results showed that the facility rights and accessibility for persons with disabilities at Health Offices in Samarinda City were still not evenly distributed, and facilities that were not friendly to persons with disabilities or were still not easily accessible to persons with disabilities and still did not meet the requirements of the needs of persons with disabilities. So it is suggested that local governments can implement facility rights and accessibility for persons with disabilities since the issuance of this regional regulation and that regional governments should consider helping and being more concerned about the rights of persons with disabilities in Samarinda City.